Pivoting to Childbirth at Home or in Freestanding Birth Centers1 in the US During COVID-19: Safety, Economics and Logistics - Daviss, Betty-Anne; Anderson, David A.; Johnson, Kenneth C. (Frontiers in Sociology, 2021)
Birth-related decisions principally center on safety; giving birth during a pandemic brings safety challenges to a new level, especially when choosing the birth setting. Amid the COVID-19 crisis, the concurrent work furloughs, business failures, and mounting public and private debt have made prudent expenditures an inescapable second concern. This article examines the intersections of safety, economic efficiency, insurance, liability and birthing persons’ needs that have become critical as the pandemic has ravaged bodies and economies around the world. Those interests, and the challenges and solutions discussed in this article, remain important even in less troubled times. Our economic analysis suggests that having an additional 10% of deliveries take place in private homes or freestanding birth centers could save almost 11 billion per year in the United States without compromising safety.